Peacemaker - Cherryh, C. J. (Cherryh, C. J. Foreigner universe., 2013)
"At last--Cajeiri has his young guests from the starship, three young folk entranced by weather and trees and creatures with minds of their own. It's all he dreamed of...But now safety is foremost: Cajeiri's grandfather has been assassinated, hostile Assassins Guild invaded Great-uncle's house, and now Bren Cameron, paidhi-aiji, who was sent to keep the aiji's son safe, has more than the young guests on his mind. The aiji-dowager knows who's to blame for the attacks, and they're going after him. The fact that the person responsible is in the heart of Assassins' Guild Headquarters, the most closely guarded fortress on the continent, is not going to stop her."--Publisher's website.